An updated network meta-analysis of EGFR-TKIs and combination therapy in the first-line treatment of advanced EGFR mutation positive non-small cell lung cancer - Qi, Yuexiao; Xia, Xiaojun; Shao, Lihua; Guo, Liyun; Dong, Yumei; Tian, Jinhui; Xu, Lijun; Niu, Ruijun; Wei, Shihong (Frontiers in Oncology, 2022)
Objectives Tyrosine kinase inhibitors (TKIs) are a standard care option in patients with non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutation. TKI-based combination treatment modes show encouraging outcomes. However, it remains unknown which is the optimal treatment as the first-line regimen for these patients on overall survival (OS). Materials and methods Randomized controlled trials and meeting abstracts that investigated EGFR-TKIs alone or in combination as front-line care for patients with NSCLC were systematically searched in relevant databases and reviewed. Fixed and random effects network meta-analysis models were used to estimate progression-free survival (PFS), OS, overall response rate, and grade three and higher adverse events (AEs). Surface under the cumulative ranking curves (SUCRAs) were used to rank treatment effects. Results Eighteen studies covering six treatments and involving a total of 4389 patients were included in this network meta-analysis. On OS, the top three treatment were first-generation EGFR-TKIs (1G EGFR-TKIs) plus chemotherapy (SUCRA, 88.1%), osimertinib (SUCRA, 65.8%) and second-generation EGFR-TKIs (2GEGFR-TKIs) (SUCRA, 63.3%). On PFS, the top three treatments were osimertinib (SUCRA, 96.0%), 1G EGFR-TKIs plus chemotherapy (SUCRA, 67.1%), and 1G EGFR-TKIs plus antiangiogenesis (SUCRA, 48.2%). Two types of TKI-based combination therapy have significantly higher risk of grade three and higher AEs than TKI alone. Conclusion 1G EGFR-TKIs plus chemotherapy and osimertinib seem to be the two better options as first-line care in advanced NSCLC patients with EGFR-mutation. Osimertinib caused the lowest incidence of AEs. However, TKIs-based combination therapy significantly increased AEs.